PERLINDUNGAN HUKUM TERHADAP KONSUMEN MELALUI SERTIFIKASI HALAL PADA PRODUK MAKANAN OLAHAN DI KOTA PALU - Marzuki Marzuki; Suhri Hanafi (ISTIQRA, 2015)
This study discusses the legal protection towards muslims` consumer through halal certification in processed food products in Palu. This is based on the writer`s anxiety witnessed the cases occurred in the community. Under various pretexts and the interests of society as consumers become victims of the behavior of processed food manufacturer irresponsible.This research is a normative combined with empirical research to determine the various factors that affect the realization of legal protection for Muslim consumers to food products processed in Palu. Namely: the law substance, Halal Certification officers, Legal Culture Society and supporting infrastructure.The results showed that the four factors that influence have not played their role to the fullest so that the conclusion that the legal protection for Muslim consumers through certification of halal processed food products in Palu has not been effective